2019
DOI: 10.7150/jca.29207
|View full text |Cite
|
Sign up to set email alerts
|

Clustered microRNAs hsa-miR-221-3p/hsa-miR-222-3p and their targeted genes might be prognostic predictors for hepatocellular carcinoma

Abstract: Objective : MicroRNAs (miRNAs) have been explored in malignancies. We investigated the functions of clustered miRNAs hsa-miR-221/222-3p in hepatocellular carcinoma (HCC). Methods : Human miRNA tissue atlas website was determined expression levels in liver tissue. Four databases, TarBase, miRTarBase, miRecords and miRPathDB, were found experimentally validated target genes of clustered miRNAs. TargetScanHuman was predicted target genes. The STRING website was depicted protein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 63 publications
2
27
1
Order By: Relevance
“…In addition, the upregulation of miR-212-3p and miR-375 exerted opposite effects on TP53 expression, respectively suppressing and promoting its transcription. Recent studies have demonstrated that miR-221-3p functions as an oncogene in specific types of human cancer, including HCC (Wang et al, 2019), non-small cell lung cancer (Yin, Zhang & Li, 2019), glioma (Milani et al, 2019), gastric cancer and breast cancer (Deng et al, 2017). It was also reported that miR-375 inhibits the proliferation and migration of many cancer cells (Guo et al, 2018;Shen et al, 2014;Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the upregulation of miR-212-3p and miR-375 exerted opposite effects on TP53 expression, respectively suppressing and promoting its transcription. Recent studies have demonstrated that miR-221-3p functions as an oncogene in specific types of human cancer, including HCC (Wang et al, 2019), non-small cell lung cancer (Yin, Zhang & Li, 2019), glioma (Milani et al, 2019), gastric cancer and breast cancer (Deng et al, 2017). It was also reported that miR-375 inhibits the proliferation and migration of many cancer cells (Guo et al, 2018;Shen et al, 2014;Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that YY1AP1 interact with NeuroG3, SS18L2, ZMYM4, ZNF496 and ZNF576 -the proteins that apart from the rst two, altered expressions in HCC is reported in literatures [19][20][21]. Regarding the two microRNAs that target YY1AP1, hsa-miR-375 is a tumor suppressor [22] while hsa-miR-222-3p shows oncogenic properties [23]. The YY1AP1 is a component of the INO80 chromatin remodeling complex, which is responsible for transcriptional regulation, DNA repair, and replication [24].…”
Section: Discussionmentioning
confidence: 97%
“…Verrier et al found that ESR1 is one of the key host factors of the liver virus and a target for the inhibition of the liver virus [ 32 ]. Wang et al also revealed that ESR1 is probably associated with HCC survival [ 33 ]. In this study, it was shown by target prediction and pathway enrichment that the bioactive compounds, glycolic acid hydrate, ginsenoside Rg1, and notoginsenoside R1, all act on the proteoglycans in cancer signal pathway and inhibit the progress of liver cancer by inhibiting the ESR1 transduction on the pathway.…”
Section: Discussionmentioning
confidence: 99%